Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Rewrite the function by completing the square.
f(x) = x^2 – 10x—96



Sagot :

Answer:

(x - 5)² -121 = 0

Step-by-step explanation:

if you need to find the roots you can take the square root of each side:

(x-5)² = 121

(x-5)² = 121

square root of (x-5)² is x-5

square root of 121 is ±11

first root:  x-5 = 11

x = 16

second root: x-5 = -11

x = -6

Answer:

[tex]f(x) = (x - 5)^{2} - 121[/tex].

Step-by-step explanation:

The goal is to rewrite [tex]f(x)[/tex] in the vertex form [tex]a\, (x - h)^{2} + k[/tex] by completing the square (where [tex]a[/tex], [tex]h[/tex], and [tex]k[/tex] are constants.)

Expand the vertex form expression:

[tex]\begin{aligned}& a\, (x - h)^{2} + k\\ &= a\, (x - h)\, (x - h) + k \\ &= a\, \left(x^2 - h\, x - h\, x + h^2\right) + k \\ &= a\, \left(x^2 - 2\, h\, x + h^2\right) + k\\ &= a\, x^2 - 2\, a\, h\, x + \left(a\, h^2 + k\right) \end{aligned}[/tex].

Compare this expression to [tex]f(x) = x^2 - 10\, x - 96[/tex] and solve for the constants [tex]a[/tex], [tex]h[/tex], and [tex]k[/tex]. Make sure that the coefficient of each term matches:

  • Coefficient for the [tex]x^2[/tex] term: [tex]a[/tex] in the expanded expression and [tex]1[/tex] in the expression for [tex]f(x)[/tex]. Hence, [tex]a = 1[/tex].
  • Coefficient for the [tex]x[/tex] term: [tex](-2\, a\, h)[/tex] in the expanded expression and [tex](-10)[/tex] in the expression for [tex]f(x)[/tex]. Hence, [tex]-2\, a\, h = -10[/tex].
  • Coefficient for the constant term: [tex]\left(a\, h^2 + k\right)[/tex] in the expanded expression and [tex](-96)[/tex] in the expression for [tex]f(x)[/tex]. Hence, [tex]a\, h^{2} + k = -96[/tex].

Substitute [tex]a = 1[/tex] into the second equation, [tex]-2\, a\, h = -10[/tex], and solve for [tex]h[/tex].

[tex]-2 \, h = -10[/tex].

[tex]h = 5[/tex].

Substitute both [tex]a = 1[/tex] and [tex]h = 5[/tex] into the third equation, [tex]a\, h^{2} + k = -96[/tex], and solve for [tex]k[/tex].

[tex]5^2 + k = -96[/tex].

[tex]k = -121[/tex].

Therefore, [tex]a\, (x - h)^{2} + k[/tex] becomes [tex](x - 5)^2 + (-121)[/tex].

Hence, the vertex form of the parabola [tex]f(x)[/tex] would be:

[tex]f(x) = (x - 5)^{2} - 121[/tex].